Determinação da massa seca, teor de nutrientes e cobertura do solo de espécies semeadas no outono-inverno - Barbosa, Carlos E. M.; Lazarini, Edson [UNESP]; Picoli, Pedro R. F. [UNESP]; Ferrari, Samuel [UNESP] (Revista Brasileira de Ciencias Agrarias, 2011)
Culture options for the autumn-winter season are a major problem for production systems under low rainfall. The aim of this study was to evaluate the effect of the sowing season on dry matter yield, nutrient content of the shoot and soil covering percentage of coverage plants on the soil on the intercrop: grain sorghum, rattlepods, pearl millet brachiaria grass and an area with weeds (fallow). The experiment was conducted under field conditions on an Oxisol (Haplustox), clay texture, in Selvíria, Mato Grosso do Sul, Brazil. The experimental design was a randomized block design with eight replications, two sowing seasons and five coverage treatments. When the sorghum culture of the first sowing season reached the harvest stage, the dry matter yield on the other treatments was evaluated. Results showed that sowing in March results in higher dry mass yield and higher soil coverage percentage in the studied species. In the first sowing season, Brachiaria brizantha presents higher dry matter yield and macronutrients extraction.
Dry mass, nutrient content and soil covering of sown species in the autumn-winter
Keywords: Brachiaria brizantha; Crotalaria juncea; Pennisetum americanum; Sorghum bicolor; Straw; Brachiaria; Crotalaria; Pennisetum glaucum; Sorghum bicolor bicolor; Urochloa brizantha